2018
DOI: 10.1287/isre.2017.0736
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Product Reviews on Product Returns

Abstract: Although many researchers in information systems and marketing have studied the effect of product reviews on sales, few have looked at their effect on product returns. We hypothesize that, by reducing product uncertainty, product reviews affect the probability of product returns. We elaborate this hypothesis starting with an analytical model that examines how changes in valence and precision of information from product reviews influence the purchase and return probabilities of risk-averse, but rational, consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(107 citation statements)
references
References 28 publications
5
98
1
3
Order By: Relevance
“…Indeed, positive reviews were found to facilitate product choice and increase sales (Chevalier & Mayzlin, 2006;Senecal & Nantel, 2004), although their effect might vary across markets, products, and consumers (Babic, Sotgiu, de Valck, & Bijmolt, 2015). A recent interesting study suggests that the variance in ratings also positively correlates with product returns (Sahoo, Srinivasan, & Dellarocas, 2013), a finding that seems consistent with our assertion that the effect of experiential information is very limited when it does not fully resolve uncertainty. Technological advances now enable consumers to have at least some direct experience online, and it is not clear how the two sources of information (self experience vs. online reviews) are combined to form overall product impression.…”
Section: Future Researchsupporting
confidence: 92%
“…Indeed, positive reviews were found to facilitate product choice and increase sales (Chevalier & Mayzlin, 2006;Senecal & Nantel, 2004), although their effect might vary across markets, products, and consumers (Babic, Sotgiu, de Valck, & Bijmolt, 2015). A recent interesting study suggests that the variance in ratings also positively correlates with product returns (Sahoo, Srinivasan, & Dellarocas, 2013), a finding that seems consistent with our assertion that the effect of experiential information is very limited when it does not fully resolve uncertainty. Technological advances now enable consumers to have at least some direct experience online, and it is not clear how the two sources of information (self experience vs. online reviews) are combined to form overall product impression.…”
Section: Future Researchsupporting
confidence: 92%
“…A more specific reputation marker that appears on Amazon (and some other platforms) ranks each sender and designates some with “top reviewer” badges (e.g., top 1,000, top 50) based on their average helpfulness ratings for each review and on the total number of reviews they have written (Amazon.com, n.d.). However, sender badges and rankings have shown inconsistent effects on receivers in terms of review helpfulness, sales, and product returns (Baek, Ahn, & Choi, ; Chen et al, ; Huang et al, ; Otterbacher, ; Pu et al, ; Sahoo, Dellarocas, & Srinivasan, ; Yazdani et al, ).…”
Section: Platformmentioning
confidence: 99%
“…Consumer ratings of WOM are widely available, though the rating system varies by platform (e.g., likes, hearts, useful votes, helpful votes). Regardless, the sum or proportion of positive ratings indicates the quality of the information provided (e.g., Chen et al, ; Ghose & Ipeirotis, ; Khern‐am‐nuai et al, ; Sahoo et al, ), and can increase trust (Packard et al, ; Resnick et al, ). Consistent with this, others’ evaluations of a source's past behavior provide a player signal of trustworthiness (Petty, Cacioppo, & Goldman, ; Shapiro, ; Weiss et al, ).…”
Section: Other Consumersmentioning
confidence: 99%
“…Altug and Aydinliyim [26] studied how consumers' discount-seeking purchase deferrals affect the return policy of online retailers and found that retailers in some conditions can gain a competitive advantage when selling to strategic consumers. Sahoo et al [27] explored the impact of online product reviews on the optimal online return strategy and showed that unbiased online reviews benefit consumers and that biasing reviews upwards results in more returns.…”
Section: Literature Reviewmentioning
confidence: 99%